Japan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Japanese Government Bond (JGB) market has been stable in Japan since the earthquake, but the factors holding down JGB yields could diminish over time. To limit these risks, fiscal policy should aim to reduce public debt quickly and lengthen maturity of JGBs. The Bank of Japan's (BoJ) easing measures have had a significant and broad-based impact on financial markets. Policies to support employment and protect incomes have been effective, but have to be phased out and complemented with training and job search assistance programs to facilitate a smooth reallocation of labor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet